Konsep Penciptaan Karya Tari Tekad Rang Padusi - Auly, Chika Alquratu (PPSDP Undergraduate Journal of Educational Sciences, 2025)
This research aims to explore the creative process behind the dance piece “Tekad Rang Padusi” which is themed around feminism. The focus is on the choreography of ‘Tekad Rang Padusi’ dance. The reference theory used is from Rully Rochayati dkk in his book titled ‘Menuju Kelas Koreografi’ (Heading to Choreography class), which identifies 10 elements: movement, space, musical accompaniment, title, theme, type of dance, number of dancers, makeup and costume, lighting, and props. Additionally, according to Prof. Dr. Sri Rochana, the stages of artistic creation include technique, exploration, and presentation. The research method used involves data collection, literature review, interviews, and observation conducted by the author. The results of the research show that the choreography is derived from traditional elements but restructured with a feminist nuance, thus creating a new atmosphere.